Identifying Resistance to the Colorado Potato Beetle (Leptinotarsa decemlineata Say) in Potato Germplasm: Review Update - Rondon, Silvia I.; Feldman, Max; Thompson, A.; Oppedisano, Tiziana; Shrestha, Govinda (Frontiers in Agronomy, 2021)
Developing plant germplasm that contains genetic resistance to insect pests is a valuable component of integrated pest management programs. In the last several decades, numerous attempts have been made to identify genetic sources of resistance to Colorado potato beetle Leptinotarsa decemlineata Say (Coleoptera: Chrysomelidae). This review focuses on compiling information regarding general L. decemlineata biology, ecology, and management focusing on discussing biochemical and morphological potato (Solanum tuberosum L.) plant traits that might be responsible for providing resistance; the review ends discussing past efforts to identify genetic material and highlights promising new strategies that may improve the efficiency of evaluation and selection of resistant material. Measurement strategies, that begin with field screening of segregating populations or wild germplasm to narrow research focus can be useful. Identifying particularly resistant or susceptible germplasm, will help researchers focus on studying the mechanisms of resistance in much greater detail which will help the development of long-term sustainable management program.